A GDSL Esterase/Lipase Catalyzes the Esterification of Lutein in Bread Wheat. Issue 12 (1st October 2019) - Watkins, Jacinta L.; Li, Ming; McQuinn, Ryan P.; Chan, Kai Xun; McFarlane, Heather E.; Ermakova, Maria; Furbank, Robert T; Mares, Daryl; Dong, Chongmei; Chalmers, Kenneth J.; Sharp, Peter; Mather, Diane E.; et al.
Abstract : The discovery of an apoplastic enzyme responsible for esterifying carotenoids that is unexpectedly spatially separated from its plastidic substrate, lutein, affords new ways to biofortify crops. Abstract: Xanthophylls are a class of carotenoids that are important micronutrients for humans. They are often found esterified with fatty acids in fruits, vegetables, and certain grains, including bread wheat ( Triticum aestivum ). Esterification promotes the sequestration and accumulation of carotenoids, thereby enhancing stability, particularly in tissues such as in harvested wheat grain. Here, we report on a plant xanthophyll acyltransferase (XAT) that is both necessary and sufficient for xanthophyll esterification in bread wheat grain. XAT contains a canonical Gly-Asp-Ser-Leu (GDSL) motif and is encoded by a member of the GDSL esterase/lipase gene family. Genetic evidence from allelic variants of wheat and transgenic rice ( Oryza sativa ) calli demonstrated that XAT catalyzes the formation of xanthophyll esters. XAT has broad substrate specificity and can esterify lutein, β-cryptoxanthin, and zeaxanthin using multiple acyl donors, yet it has a preference for triacylglycerides, indicating that the enzyme acts via transesterification. A conserved amino acid, Ser-37, is required for activity. Despite xanthophylls being synthesized in plastids, XAT accumulated in the apoplast. Based on analysis of substrate preferences and xanthophyll ester formation in vitro and in vivo using xanthophyll-accumulating rice callus, we propose that disintegration of the cellular structure during wheat grain desiccation facilitates access to lutein-promoting transesterification.